Abiotic treatment of PCP-contaminated water with metallic iron. - Beaudet, France. (University of Ottawa (Canada), 1994)
The removal of PCP from aqueous solution in contact with metallic iron was investigated by laboratory batch experiments. The decline in PCP concentration as well as inorganic parameters were monitored over time. Removal of up to 90% of the initial PCP was observed within 24 hours. The initial geochemical conditions of the PCP solution changed rapidly to basic and reductive conditions when in contact with metallic iron. Organic degradation by-products were not found during the removal of PCP using two distinct analytical procedures. Chloride ions analyzed in the solution after PCP removal were relatively low and showed high variability between experiments. The extraction of iron with solvents showed that a maximum of 37% PCP was sorbed. The effectiveness of iron on PCP removal appeared to be limited by the number of contacts with a fresh PCP solution. The rate constant in PCP removal appeared to be directly proportional to the iron to solution ratio. The PCP removal behaviour fitted well two sorption models (Freunlich, Langmuir). The results indicate that the process involved in the removal of PCP does not seem to be dechlorination because of the lack of by-products and low level in chloride ion, and is not completely sorption because of the lack of reversibility.
Keywords: Engineering, Chemical.